This was America, 1865-1965 : unequal citizens in the segregated republic - Korman, Gerd (North American Jewish studies., 2022)
"By examining experiences of Jewish Americans in the hundred years between the American Civil War and the African American Civil Rights Revolution, this book focuses on citizens of the republic, each of whom usually spent their daily lives in black and white "republican peoplehoods." In a Euro-American network of information moving freight, forced laborers, and paying passengers, some of the white ones, commanding the nation's "public square," structured a segregated republic and capitalist society lasting during WWII. Then it was that the information network brought news about the war's genocidal Final Solution, about the Holocaust that murdered millions of Jews. This political economy sustained a hierarchy of privatized ethnic groups, whose race and religion, in their norms of "ethnicking," was used to deprive them of legal and equal collective standing in the United States. "This Was America" is a book about those privatized identities that the years of the Civil Rights Revolution would bring into the public square of the nation's republic"--